Respuestas

2012-05-20T18:09:22+02:00

a) 3x - 5 + 2x = x + 3
    -5-3 = x-2x-3x
    -8 = -4x
      -8/-4 = x
      2 = x

 b) 8 - 2 (x + 1) = 5 (x - 1) + 4

  8-2x-2 = 5x-5+4
  8-2-4+5 = 2x-5x
 7 = -3x
7/-3 = x
 

2012-05-20T18:45:19+02:00

buenas tasrdes.a)3x-5+2x=x+3            
                         3x+2x-x=3+5
                         4x=8

                         x=8/4
                         x=2

comprobacion:
                         3(2)-5+2(2)=2+3
                           6-5+4=5
                             5=5 

8-2(x+1)=5(x-1)+4
8-2x-2=5x-5+4
-2x-5x=-5+4+2-8

-7x=-7
x=-7/-7
x=1                               comprobacion:8-2(1)+1)=5(1)-1)+4
                                                         8-2(1)-2=5(1)-5+4
                                                         -2(1)-5(1)=-5+4+2-8
                                                          -7(1)=-7
                                                           -7=-7              saludos.